Hypolipidemic activity of aqueous extract of Withania coagulans dunal in albino rats - Hemalatha S.; Wahi A.K.; Singh P.N.; Chansouria J.P.N. (My University, 2025)
Administration of an aqueous extract of fruits of Withania coagulans (1 g/kg; p.o.) to high fat diet induced hyperlipidemic rats for 7 weeks, significantly reduced elevated serum cholesterol, triglycerides and lipoprotein levels. This drug also showed hypolipidemic activity in triton induced hypercholesterolemia. The histopathological examination of liver tissues of treated hyperlipidemic rats showed comparatively lesser degenerative changes compared with hyperlipidemic controls. The hypolipidemic effect of W. coagulans fruits was found to be comparable to that of an Ayurvedic product containing Commiphora mukkul. Copyright © 2006 John Wiley & Sons, Ltd.